Mass and number concentration distribution of marine aerosol in the Western Pacific and the influence of continental transport. (1st April 2022) - Ma, Yining; Zhang, Xiangguang; Xin, Jinyuan; Zhang, Wenyu; Wang, Zifa; Liu, Quan; Wu, Fangkun; Wang, Lili; Lyu, Yilong; Wang, Qinglu; Ma, Yongjing
Abstract: We quantify for the first time marine aerosol properties and their differences in the offshore and remote ocean in the mid-latitude South Asian waters, low-latitude South Asian waters, and equatorial waters of the Western Pacific Ocean, based on shipboard cruise observations conducted by the Western Pacific Ocean Scientific Observation Network in winter 2018, and further investigate the effects of long-range transport of continental aerosols on the marine environment. During the overall observation period, the average number concentration of particle matter which aerodynamic diameters<2.5 μm (PM2.5N ) was 35.1 ± 87.4 cm −3 and the mass concentration (PM2.5M ) was 12.3 ± 9.1 μg/m 3 . The PM2.5N and PM2.5M during the continental air mass transport period were 7.2 and 1.3 times higher than those during the non-transport period (109.2 ± 169.3 cm −3, 15.9 ± 14.9 μg/m 3 ), respectively. Excluding transport period, the average PM2.5N and PM2.5M are reduced by 120% and 7%. Coarse mode particle number concentration (PM2.5–10N ) and mass concentration (PM2.5–10M ) are not significantly influenced by continental air masses (only a reduction of 7% and 2%). The variation of marine aerosol concentrations in different latitudes zones is greatly influenced by continental aerosol transport. The offshore PM2.5M /PM10M was 30%, 21%, and 22% in the mid-latitude sea of South Asia, a low-latitude sea of South Asia, and the equatorial sea, respectively. In comparison, in the remote ocean, the distribution ratio of PM2.5M /PM10M tended to be steady (22%–23%), and the background characteristics of marine aerosols were clearly represented. The aerosol concentration decreases with the increase of wind speed during the transport period, and the wind speed reflects the scavenging effect on aerosol. In the non-transport period, the wind speed at the sea surface promotes the generation of marine aerosols, and the impact in wind speed is strongest in the PM2.5 –PM5 particle size range. Graphical abstract: Schematic diagram of the distribution of aerosols in the western Pacific Ocean at different latitudes and offshore distance. The pie chart represents the particle size composition of different latitudinal zones. Image 1 Highlights: Large differences in aerosol distribution between near-land and open-ocean area. Continental transport lead to increase in the proportion of fine particles. Continental transport affects near-land aerosol distribution to varying degrees. Different wind speed responses to transport and non-transport period.